Effect of Sphaerosporella brunnea mycorrhizas on mycorrhization of Quercus ilex × Tuber melanosporum (New Zealand Journal of Crop and Horticultural Science, 2008)
Abstract It is generally accepted that Sphaerosporella brunnea is a significant ectomycorrhizal contaminant in nurseries producing plants mycorrhized with various species of Tuber, and subsequently in truffières after outplanting. At the University of Alcalá, Spain, 397 small plants of Quercus ilex which were mycorrhized with Tuber melanosporum were inadvertently contaminated with S. brunnea, and this contamination was then monitored for 2 years. Sixty percent of the plants were contaminated and had S. brunnea ascomata on the surface of the container on one or several occasions. However, a Spearman test provided no evidence that S. brunnea mycorrhizas affected T. melanosporum mycorrhization whereas other contaminating ectomycorrhizal fungi significantly did. Therefore, it appears that S. brunnea is not detrimental to plants which are well mycorrhized with T. melanosporum.
doi: 10.1080/01140670809510231

Problems of using rockroses in Tuber melanosporum culture: soil and truffle harvest associated with Cistus laurifolius (Agroforestry Systems, 2007)
The Pe´rigord black trufﬂe (Tuber melanosporum Vittad.) can mycorrhize with rockroses (Cistus L.) in Mediterranean forests. These shrubs may be of interest for trufﬂe cultivation as they produce early carpophores, collaborate in tree mycorrhization and in the survival of Tuber melanosporummycelium. However, there are very few quantitative studies on trufﬂe production associated with Cistus. For this reason, we have carried out a study on the natural production of Tuber melanosporum associated with Cistus laurifolius L. in central Spain. An Anova test conﬁrmed the existence of signiﬁcant differences in carpophore production in four habitats, with and without the presence of C. laurifolius. Twenty-one burns associated with C. laurifolius showed less signiﬁcant production than the rest. We also conﬁrmed that in 122 burns, Tuber melanosporum was always unequivocally associated with the root base of Quercus L. or Corylus L. trees. Similarly, ﬁve trufﬂe-collectors conﬁrmed that they had never found a single burn with carpophore production associated exclusively with rockroses. It has also been statistically veriﬁed that many Cistus die in Tuber melanosporum burns, whereas in old burns with minimum carpophore production, a new colonization of young Cistus has been observed. This study also conﬁrms that C. laurifolius mycorrhizes easily with Tuber melanosporum. We propose that Cistus laurifolius may act as transmitters of Tuber melanosporum, although they do not induce fruiting. Consequently, the commercial cultivation of Cistus laurifolius mycorrhized with Tuber melanosporum for production is not recommended in trufﬂe culture. The results reported substantiate the negative observations in cultivations ofT. melanosporum with other Cistusspecies.